Development and validation of food and nutrition literacy instrument in young people, Turkey: Food and Nutrition Literacy Instrument, Methodology Study - Demir, Gülcan; Özer, Ali (Progress in Nutrition, 2022)
Background and aim: To evaluate food and nutrition literacy, measurement tools that include declarative, procedural, and subjective knowledge output are needed. The present study aimed to develop a valid and reliable measurement tool that can evaluate FNL holistically in young people.Methods: This study was developed in nine steps under three phases:1) item development and content validity, 2) scale development including pre-testing of questions, sampling and survey administration (by sex with the quota sampling method), item reduction strategies, extraction of factors (exploratory factor analyses), and 3) scale evaluation including confirmatory factor analyses, reliability analyses (Cronbach’s α, KR-20, intraclass correlation coefficient) and differentiation by “known groups” with total of 538 young people.Results: The instrument consisted of knowledge, attitude, and behavior domain dimensions: (1) knowledge as five factors and (2) attitude and behavior as four factors. After the analysis of the FNL instrument, 51 items were removed from 87 items. The final instrument has 36 items, of which 13 were in the domain of knowledge, 13 in the domain of attitude, and 10 in the domain of behavior. The total variance explained by the domain dimensions of the instrument was ≥55%. The confirmatory factor analysis fit indices were good. There was satisfactory internal reliability for the domain dimensions (≥0.60). There was external test-retest reliability (ICC ≥ 0.84). Women’s knowledge level regarding criterion validity was higher than that of men, and the difference was statistically significant (p < 0.05).Conclusions: This 36 item, three domains dimensional FNL instrument can be used to assess food and nutrition literacy in young people. It can be used to assess and improve food and nutrition literacy in university settings.